Syntheses, structures, photoluminescence, and magnetism of a series of 3, 5-di(3, 4-dicarboxylphenyloxy)benzoate-based complexes tuned by N-donor co-ligands and transition metal ions. (1st February 2019) - Zhang, Ju-Wen; Li, Jia-Xuan; Ren, Yu-Ning; Man, Yi; Liu, Bin-Qiu; Dong, Yan-Ping
Graphical abstract: Six metal polycarboxylate complexes tuned by N-donor co-ligands and transition metal ions have been successfully synthesized and structurally characterized. The photoluminescent and magnetic properties of partial complexes were studied. Abstract: Six transition metal–organic complexes based on 3, 5-di(3, 4-dicarboxylphenyloxy)benzoic acid (H5 L) and different N-donor co-ligands, namely, Cu(H3 L)(2, 2′-bpy)·H2 O (1 ), Zn2 (HL)(2, 2′-bpy)2 (2 ), Cd2 (HL)(2, 2′-bpy)2 (H2 O) (3 ), Cd2 (HL)(phen)4 ·5H2 O (4 ), Cu(H3 L)(phen) (5 ), and Cu(H3 L)(4, 4′-bpy)·H2 O (6 ) (2, 2′-bpy = 2, 2′-bipyridine, phen = 1, 10-phenanthroline, 4, 4′-bpy = 4, 4′-bipyridine), were successfully synthesized under hydrothermal conditions. Their structures were determined by single-crystal X-ray diffraction analyses and further characterized by elemental analyses, IR, powder X-ray diffraction (PXRD), and thermogravimetric analyses (TGA). Complexes1 and5 possess discrete zero-dimensional (0D) structures which are further assembled into three-dimensional (3D) supramolecular frameworks by hydrogen-bonding interactions and π–π stacking interactions. Complexes2 and3 display similar 3D frameworks with different topologies. Complex4 shows a one-dimensional (1D) chain which is further connected into a two-dimensional (2D) supramolecular layer via π–π stacking interactions. Complex6 exhibits a 1D chain which is further extended into a 3D supramolecular network through hydrogen-bonding interactions. The H5 L ligand is partially deprotonated in1 –6 . The N-donor co-ligands and transition metal ions have important effects on the architectures of1 –6 . The photoluminescent properties of2 –4 and the magnetic properties of1 and6 were also studied.